Sequential administration of the high affinity CXCR4 antagonist BKT140 promotes megakaryopoiesis and platelet production. (1st August 2013) - Abraham, Michal; Weiss, Ido D.; Wald, Hanna; Wald, Ori; Nagler, Arnon; Beider, Katia; Eizenberg, Orly; Peled, Amnon
Summary Platelets are the terminal differentiation product of megakaryocytes (MKs). Cytokines, such as thrombopoietin (TPO), are known to influence different steps in MK development; however, the complex differentiation and platelet localization processes are not fully understood. MKs express the receptor CXCR4 and have been shown to migrate in response to CXCL12 and to increase their platelet production. In this study, we studied the role of CXCR4 in platelet production with the high affinity CXCR4 antagonist, BKT140. Single and sequential administration of BKT140 significantly increased the number of MKs and haematopoietic progenitors (HPCs) within the bone marrow (BM). Increased megakaryopoiesis was associated with increased platelet production. Single and sequential administration of BKT140 also increased the number of HPCs in the blood. In a model of 5‐fluorouracil‐induced thrombocytopenia, BKT140 significantly reduced the severity and duration of thrombocytopenia and cytopenia when administered before and after chemotherapy. Our results demonstrated that the CXCR4 antagonist, BKT140, mediated unique beneficial effects by stimulating megakaryopoiesis and platelet production. These results provide evidence for the possible therapeutic use of BKT140 for modulating platelet numbers in thrombocytopenic conditions.